2012
DOI: 10.1007/s00467-012-2320-8
|View full text |Cite
|
Sign up to set email alerts
|

HDAC inhibitors in kidney development and disease

Abstract: The discovery that histone deacetylase inhibitors (HDACis) can attenuate acute kidney injury (AKI)-mediated damage and reduce fibrosis in kidney disease models has opened the possibility of utilizing HDACis as therapeutics for renal injury. Studies to date have made it abundantly clear that HDACi treatment results in a plethora of molecular changes, which are not always linked to histone acetylation, and that there is an essential need to understand the specific target(s) of any HDACi of interest. New lines of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 112 publications
1
31
0
Order By: Relevance
“…HDACis are known to have distinct effects on cell cycle checkpoint arrest, DNA instability and repair mechanisms in transformed versus primary cells. 43,44 In addition, the HDACi TSA stimulates cell proliferation at digit amputation sites in mice, 45 indicating that HDACis may have proliferative effects during tissue regeneration. Our data show that m4PTB increases expression of a large number of genes that promote cell cycle progression (Supplemental Table 1), particularly the G2/M phase of the cell cycle (Supplemental Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…HDACis are known to have distinct effects on cell cycle checkpoint arrest, DNA instability and repair mechanisms in transformed versus primary cells. 43,44 In addition, the HDACi TSA stimulates cell proliferation at digit amputation sites in mice, 45 indicating that HDACis may have proliferative effects during tissue regeneration. Our data show that m4PTB increases expression of a large number of genes that promote cell cycle progression (Supplemental Table 1), particularly the G2/M phase of the cell cycle (Supplemental Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Several small molecule inhibitors of SIRTs were reported recently, such as splitomicin and its derivatives, sirtinol, AGK2, cambinol, suramin and tenovin [24]. Class I and II HDACs inhibitors exert anti-inflammatory and anti-fibrotic effects in kidney diseases [32]. Inhibition of the SIRT2 pathway is also anti-fibrotic.…”
Section: Discussionmentioning
confidence: 99%
“…HDAC inhibition exerts anti-fibrotic and anti-inflammation functions in numerous animal models of kidney diseases [37,38]; however, the particular HDAC isotypes involved in different disease models or cell types are not fully revealed. Recent studies showed that HDAC2 [39] was upregulated by TGF-β in diabetic kidney and HDAC4 [40] was involved in STZ-induced diabetic rat model, indicating that one or several HDAC members might be actively involved in a specific disease setting.…”
Section: Discussionmentioning
confidence: 99%